Reconstruction Of Status And Material Content Of The People's Consultative Assembly Legal Products In Indonesia - Ela Nurlela (Nurani Hukum, 2021)
The current constitutional dynamics have negated the People's Consultative Assembly (MPR) authority to issue legal products (regelling) through amendments to the 1945 Constitution and have resulted in equal standing between state institutions. So that several problems arise as an implication of the change in the powers of the MPR, for example regarding the state planning system, the existence of the existing MPR Decree in the statutory system of law, and the implications for the Indonesian constitutional system which confuse the MPR's authority as a state institution. This paper will also contain several changes and ideas in the constitutional system to answer various problems, through repositioning the position of the MPR, forming a legal product review body for the MPR, and implementing the fifth amendment to the 1945 Constitution, and arranging Indonesian legislation.